“Asfixia perinatal: Factores de riesgo en el parto vaginal Hospital de Apoyo N° 3 Salud – Chepén, 1990 – 1992” - Terry Arellano, Leonor Consuelo (1994)
A study of 1,781 R.N.V. Product of 1,752 vaginal births attended at the Maternity Hospital of support No. 3 - Health - Chepén in the period from January 1, 1990 to December 31, 1992; Selecting 73 stories corresponding to R.N. With APGAR less than 7 a minute and five minutes, according to the inclusion criteria; Which were compared with a random sample of 177 R.N. Whose APGAR a minute score was 7 to 10; With the objective of determining the incidence of perinatal asphyxia according to degree of severity, identify risk factors (maternal, fetal and mechanical) through relative risk, associated complications and specific mortality of perinatal asphyxia in the last 3 years. The incidence of perinatal asphyxia found is similar to that of other authors. The relative risk of maternal, fetal and mechanical factors in vaginal delivery was found to be the most significant to non-prenatal control, maternal age under 20 years and over 35, multiparity, anemia, toxemia, RPMD, prematurely IUGR, presentation Breech, twin pregnancy, prolonged expulsive and dystocic parturition as causes of perinatal asphyxia. The complications observed in the R.N. With asphyxia was related to the intensity of the previous obstetric asphyxia and the techniques of resuscitation in the delivery room. The asphyxia mortality rate is almost similar to that reported by other authors in different parts of the country, being the main cause of perinatal mortality. Finally, a card is presented for the identification of the risk of perinatal asphyxia during pregnancy, which can be used as an instrument to identify the woman who is prone to having a R.N. With perinatal asphyxia decreasing maternal and perinatal morbidity and mortality; And thus facilitate future research (Annex 3).